Sponge particulates for biomedical applications: Biofunctionalization, multi-drug shielding, and theranostic applications. (June 2021) - Zhang, Huaqing; Jin, Yi; Chi, Cheng; Han, Guochen; Jiang, Wenxin; Wang, Zhen; Cheng, Hao; Zhang, Chenshuang; Wang, Gang; Sun, Chenhua; Chen, Yun; Xi, Yilong; et al.
Abstract: Sponge particulates have attracted enormous attention in biomedical applications for superior properties, including large porosity, elastic deformation, capillary action, and three-dimensional (3D) reaction environment. Especially, the tiny porous structures make sponge particulates a promising platform for drug delivery, tissue engineering, anti-infection, and wound healing by providing abundant reservoirs of broad surface and internal network for cargo shielding and shuttling. To control the sponge-like morphology and improve the diversity of drug loading, some optimized preparation techniques of sponge particulates have been developed, contributing to the simplified preparation process and improved production reproducibility. Bio-functionalized strategies, including target modification, cell membrane camouflage, and hydrogel of sponge particulates have been applied to modulate the properties, improve the performance, and extend the applications. In this review, we highlight the unique physical properties and functions, current manufacturing techniques, and an overview of spongy particulates in biomedical applications, especially in inhibition of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infectivity. Moreover, the current challenges and prospects of sponge particulates are discussed rationally, providing an insight into developing vibrant fields of sponge particulates-based biomedicine. Graphical abstract: Image 1